2014
DOI: 10.1111/ajt.12524
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DXA and Quantitative CT Measures of Musculoskeletal Outcomes Following Pediatric Renal Transplantation

Abstract: This prospective study evaluated changes in DXA whole body bone mineral content (WB-BMC) and spine areal bone mineral density (spine-BMD), and tibia quantitative CT (QCT) trabecular and cortical volumetric BMD and cortical area in 56 children over 12 months following renal transplantation. At transplant, spine-BMD Z-scores were greater in younger recipients (<13 years), vs. 898 reference participants (p<0.001). In multivariate models, greater decreases in spine-BMD Z-scores were associated with greater glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…It has previously been demonstrated that this relationship occurs because cortical BMD varies in such a narrow range that BMC is almost entirely a function of bone size [18, 30]. Our data in AN are consistent with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has previously been demonstrated that this relationship occurs because cortical BMD varies in such a narrow range that BMC is almost entirely a function of bone size [18, 30]. Our data in AN are consistent with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…However, these children had significantly lower mean pQCT trabecular vBMD Z-scores and significantly greater cortical vBMD Z-scores than the reference population [17]. Similar discrepancies between DXA and pQCT have been seen in studies of pediatric patients with Crohn disease and cystic fibrosis [18, 19]. …”
Section: Introductionmentioning
confidence: 80%
“… reported an elevated trabecular volumetric BMD (by peripheral quantitative computed tomography examination) in younger RTR and a significant decrease in association with greater glucocorticoid exposure. More recently, normal values of BMD z scores were obtained in children with RTx both at the time of transplantation and 12 months, however, with a significant decrease occurring over this period . Similarly, mean BMD z scores adjusted for HAZ showed better mineralization levels in our patients at the time of RTx and osteopenia was present in only 12% (n = 3).…”
Section: Discussionsupporting
confidence: 63%
“…As children with suspected osteopathology are often also affected by chronic disease or endocrine disorders resulting in deviant growth, a further correction of the Z-score for the actual height of the patient is necessary[ 2 , 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%